Analisis Teknologi Komunikasi Terhadap Bisnis Modern Pada Perusahaan Apple Inc: Meninjau Dampak Teknologi Modern Terkini Pada Operasi Bisnis di Perusahaan Apple Inc - Hilma Harmen; Aprinawati Aprinawati; Oscar Majeovan Surbakti; Rizky Ramadhan; Jonatan Gerald; Mochamad Rakel Junaedi; Doly Siregar; Febrian Fadlan Reynaldi (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to analyze the international business perspective on the leading technology company, Apple Inc. In an era of increasingly advanced globalization, international business has become an important factor in company growth and success. The research method used is descriptive analysis by collecting secondary data from various sources such as financial reports, industry publications and related academic articles. Communications technology has become a major force in changing the modern business landscape. Leading technology companies such as Apple Inc. is an important example of how the application of communications technology impacts business operations and strategy. This research aims to investigate the influence of communication technology on modern business at Apple Inc. This research uses a qualitative approach by collecting data from various sources, including related literature, news analysis, and Apple's financial reports. The results of the analysis show that communications technology has had a major impact on Apple's business, both in terms of product development, marketing and customer service. In product development, Apple has utilized communications technology to increase innovation and efficiency. Through communication platforms such as video conferencing and online collaboration, Apple development teams can work effectively even in different locations around the world. Apart from that, communication technology also allows Apple to interact more closely with customers, whether through social media, online customer service, or direct communication platforms such as instant messaging. However, there are also challenges that Apple faces in adopting communication technology. One of them is the issue of data privacy and security, which is increasingly important amidst increasing public attention to data privacy. Apple has attempted to address these challenges through innovations in encryption technology and strict privacy policies.